Determinant Factors of Teacher Quality in State Islamic Elementary Schools - Fahrezi, Muhammad; Siahaan, Amiruddin; Nahar, Syamsu (Fitrah: Journal of Islamic Education, 2024)
The quality of education in madrasah ibtidaiyah is a critical concern, as it depends heavily on teacher competence, leadership, and institutional management. This study examines the concept of educational quality, teacher development planning, leadership in quality improvement, and models of teacher quality enhancement in madrasah ibtidaiyah. Employing a qualitative approach with a multisite design, the research was conducted at MIN 9 Medan and MIN 12 Medan. Data were gathered through observation, interviews, and documentation, and analyzed both within and across sites. The findings indicate that educational quality is shaped by the synergy of effective learning, Islamic character formation, visionary leadership, participatory management, and teacher professionalism. Teacher development planning is carried out in short, medium, and long-term stages through needs assessment, competency programs, supervision, learning communities, partnerships, recognition, and continuous monitoring-evaluation. Leadership is transformational and participatory, fostering a culture of self-directed professional growth. The proposed teacher development model is systematic and sustainable, integrating training, supervision, collaboration, and character building. This study highlights the need for synergy among leadership, management, and professionalism to strengthen the quality of madrasah ibtidaiyah.